ASSOCIATION BETWEEN BODY IMAGE AND STRESS LEVELS AMONG ADOLESCENTS: A CROSS-SECTIONAL STUDY AMONG STUDENTS OF MADRASAH ALIYAH NEGERI 1 MEDAN - Cindy Amalia Daulay; Amelia Eka Damayanty (MEDALION Journal: Medical Research, Nursing, Health and Midwife Participation, 2026)
Approximately 14% of adolescents experience mental health disorders, including stress, while in Indonesia an estimated 9.8% of adolescents experience stress and depression. During adolescence, physical changes, beauty standards, social media exposure, and peer influence may negatively affect body image, increasing psychological distress. This study aimed to analyze the relationship between body image and stress levels among students at Madrasah Aliyah Negeri 1 Medan. A correlational study with a cross-sectional design was conducted among 92 students in grades X and XI selected using consecutive sampling. Body image and stress levels were assessed using the Body Appreciation Scale-2 (BAS-2) and the Perceived Stress Scale-10 (PSS-10), respectively. Data were analyzed using Spearman's rank correlation test. Most respondents were 15 years old (69.6%) and female (52.5%), with the majority reporting moderate body image (51.1%) and moderate stress levels (56.5%). Spearman's rank correlation showed a significant negative association between body image and stress levels (r = −0.634, p < 0.001), indicating that students with more positive body image tended to report lower perceived stress. These findings suggest that promoting positive body image may contribute to reducing stress and supporting mental health among adolescents